(untitled) (Journal of Plant Disease Sciences, 2023)
Citrus root rot caused by Phytophthora parasitica var. nicotianae is the most damaging disease in citrus cultivation in Maharashtra’s Vidarbha region. To overcome the damage caused by this disease, tolerant/resistant rootstocks must be selected. In present study, twelve varied root stocks were tested in sick pot condition to determine tolerance/resistance against Phytophthora nicotianae during 2020-21 by inoculating 6 month old seedlings with a 20 ml spore suspension (108 cfu/ml) of P. nicotianae per pot. Disease incidence, feeder root rot index, percent leaf fall and Phytophthora population density were all assessed six weeks after inoculation. The response of root stocks to the tested pathogen varied. The minimum per cent root rot incidence (4.44 %) and feeder root rot (0.63) was observed in Alemow (C. macrophylla) while maximum root rot incidence (28.89%) and feeder root rot (3.20) was noticed in susceptible check Rough lemon (Citrus jambheri). Rangpur lime Akola had the highest seedling height (28.43 cm), while root stock CRH-12 had the lowest (21.07 cm). The results showed that there were no significant differences in the population density of Phytophthora cfu/cc soil in the tested root stocks. It is thought that the rootstock Alemowisinvolvedin citrusplant tolerantto P. nicotianae.